Asynchronous transfer mode (ATM) network performance measures - Lee, Yew Fai. (2010)
ATM cells which are transported over the ATM network experience random delays in the network while reaching the destination. This variation in delay is known as cell delay variation (CDV) which is one of the important parameters of ATM network performance measures. The CDV is mainly due to the queuing in multiplexing stages which alter the initial time structure of the cell streams in the network. This project presents a qualitative analysis of the CDV through a computer simulation of constant Bit Rate (CBR) traffic multiplexed with some Pursty traffic on a 5 node ATM network. Bursty ATM traffic arrives at each of the network elements according to the Markov Modulated Poisson Process (MMPP), while CBR traffic is generated at a constant rate to the network. The distribution of the cell delay (CD) and cell delay variation (CDV) in a constant bit rate traffic multiplexed with each of the 3 different classes of bursty traffic is analysed